2014
DOI: 10.1007/s40615-014-0050-2
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccine Knowledge and Attitudes, Preventative Health Behaviors, and Medical Mistrust Among a Racially and Ethnically Diverse Sample of College Women

Abstract: Awareness of medical mistrust and the influence on health behaviors may aid in increasing delivery of quality health services for racial and ethnic minority populations. Further research among different populations is needed to elucidate impacts of medical mistrust and provider communication on preventative health behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
4
34
0
Order By: Relevance
“…While fewer studies have focused on understanding the link between medical mistrust and prevention of STIs, recent research has shown that women with higher mistrust were less likely to have engaged in preventive health behaviors such as HPV immunization, a trend that was exacerbated when patients and providers were racially discordant [34]. This finding has significant public health implications given higher rates of HPV prevalence and cervical cancer incidence and mortality and lower rates of HPV vaccine completion in Black and Latina women, compared to White women [3537].…”
Section: Discussionmentioning
confidence: 99%
“…While fewer studies have focused on understanding the link between medical mistrust and prevention of STIs, recent research has shown that women with higher mistrust were less likely to have engaged in preventive health behaviors such as HPV immunization, a trend that was exacerbated when patients and providers were racially discordant [34]. This finding has significant public health implications given higher rates of HPV prevalence and cervical cancer incidence and mortality and lower rates of HPV vaccine completion in Black and Latina women, compared to White women [3537].…”
Section: Discussionmentioning
confidence: 99%
“…This secondary data analysis is part of a larger study ( Hernandez et al, 2017 ; Kolar et al, 2015 ; Wheldon, Kolar, Hernandez, & Daley, 2017 ). Data were from a non-probability based cross-sectional survey of ethno/racial minority students attending a large Southeastern university in the fall of 2011.…”
Section: Methodsmentioning
confidence: 99%
“…Eighteen of the quantitative studies did not contain a definition of trust or a discussion of the concepts present within the trust literature, despite explicitly mentioning trust within their aim or research question. 37 , 39 , 41-44 , 46 , 48 , 49 , 51-54 , 56 , 58 , 60 , 61 , 64 By leaving the definition of trust implicit, these papers created ambiguity around this core concept. Four studies 38 , 47 , 50 , 63 included some brief mentions of relevant trust concepts (e.g.…”
Section: Quantitative Studiesmentioning
confidence: 99%